Social Skills in Intellectual Disability: A Critical Overview and Future Research Directions in Morocco - Ismail Iraqui Houssaini; Otman Kaddouri; Abdelilah Bousseta; Mohammed Jabbad; Aicha Ziani (International Journal of Education, Culture, and Society, 2026)
Although social skills deficits are widely recognized as a core characteristic of intellectual disability and have been extensively examined in international scientific literature, knowledge on this issue remains limited and fragmented in Moroccan publications. This study aims to provide a focused overview of the major findings on social skills among individuals with intellectual disability, while also assessing the current status of scientific research in the Moroccan context and identifying directions for future inquiry. The review shows that published studies on intellectual disability in Morocco have largely concentrated on demographic, clinical, social, and rights-related institutional dimensions, with little to no attention given to the assessment of social skills, social functioning, or related deficits. This critical gap contributes to uncertainty and weakens conceptual and practical understanding among researchers and practitioners. The analysis further highlights the absence of clear theoretical and methodological frameworks in Moroccan scholarship that could support rigorous investigation and evidence-based clinical practice for individuals with intellectual disability. The study concludes that there is a pressing need to establish a dedicated line of research on social skills and social functioning among Moroccan individuals with intellectual disability. This overview contributes by clarifying the current state of knowledge, identifying major scholarly gaps, and offering a basis for future research development in the field.